The Nisga'a Treaty : Polling Dynamics and Political Communication in Comparative Context - Ponting, J. Rick (Book collections on Project MUSE., 2006)
The Nisga'a Treaty presents an inside story of the socio-political dynamics behind the massive polling and advertising campaign through which the Government of British Columbia "sold" the Nisga'a Treaty to British Columbians. A complementary chapter on the polling done on the Aboriginal reconciliation issue in Australia provides further international context. J. Rick Ponting's research draws from archival sources, stunningly frank Freedom of Information documents, and lengthy interviews with bureaucratic and political elites. This book has two purposes: to contribute to the understanding of an important event in the history of relations between government and Indigenous people in British Columbia and Australia, and to contribute to an understanding of the dynamics of public opinion polling in all its phases. The book explores the processes of marketing government policy to the public, which is to say, the shaping of public opinion. Accordingly, it speaks directly to the basic democratic issue of whether governments should lead, follow, or ignore public opinion on important policy issues.